Teaching Notes of Cases: Real World Challenges Towards Business Excellence - Noraina Mazuin, Sapuan (Penerbit UMPSA, 2025)
This teaching notes is a comprehensive resource for educators and business students, this collection guides critical thinking, problem solving and strategic decision making through structured teaching notes.